2017
DOI: 10.1111/den.12922
|View full text |Cite
|
Sign up to set email alerts
|

Associations between drugs and small‐bowel mucosal bleeding: Multicenter capsule‐endoscopy study

Abstract: Background and Aim: Although several drugs may induce small-bowel mucosal injuries, it is unclear whether these injuries contribute to overt small-bowel bleeding. This study was designed to evaluate the associations between drug use and small-bowel mucosal injury and between these mucosal injuries and overt bleeding in a disease-relevant population. Methods:We retrospectively studied patients with suspected small-bowel diseases who underwent capsule endoscopy between 2010 and 2013. Drug exposure, Charlson Como… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…SBCE can visualize the entire small‐intestinal mucosa and facilitate visualization of small‐intestinal abnormalities. Several studies have confirmed the efficacy of SBCE for certain disorders, such as small‐bowel (SB) bleeding, suspected and diagnosed Crohn's disease (CD), SB malignant tumors, and small‐intestinal mucosal injury associated with use of non‐steroidal anti‐inflammatory drugs …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SBCE can visualize the entire small‐intestinal mucosa and facilitate visualization of small‐intestinal abnormalities. Several studies have confirmed the efficacy of SBCE for certain disorders, such as small‐bowel (SB) bleeding, suspected and diagnosed Crohn's disease (CD), SB malignant tumors, and small‐intestinal mucosal injury associated with use of non‐steroidal anti‐inflammatory drugs …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have confirmed the efficacy of SBCE for certain disorders, such as small-bowel (SB) bleeding, suspected and diagnosed Crohn's disease (CD), SB malignant tumors, and small-intestinal mucosal injury associated with use of non-steroidal anti-inflammatory drugs. 2 Since SBCE's introduction, there has been progress of not only SBCE devices (e.g. wider field of view, analytical software) but also regimens of the SBCE procedure (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the impact of capsule endoscopy on clinical outcomes remains controversial despite reports of SB mucosal damage in 70% of patients taking NSAIDs, 22,40 because it remains unclear whether SB mucosal injuries contribute to signi cant bleeding. 41 Although patients with NSAID-induced SB injury show low frequency of severe bleeding in the SB, 42 rebleeding rates of 21-35% have been reported in patients with SB ulcerations during a mean follow-up period of 17.1-29.7 months. 15,43 These reports suggest a clinical implication of SB ulcers, which cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the impact of capsule endoscopy on clinical outcomes remains controversial despite reports of SB mucosal damage in 70% of patients taking NSAIDs, 22,39 because it remains unclear whether SB mucosal injuries contribute to significant bleeding. 40 Although patients with NSAIDinduced SB injury show low frequency of severe bleeding in the SB, 41 rebleeding rates of 21-35% have been reported in patients with SB ulcerations during a mean follow-up period of 17.1-29.7 months. 15,42 These reports suggest a clinical implication of SB ulcers, which cannot be ignored.…”
Section: Discussionmentioning
confidence: 99%